2021
DOI: 10.1183/13993003.00265-2021
|View full text |Cite
|
Sign up to set email alerts
|

Awake prone positioning and oxygen therapy in patients with COVID-19: the APRONOX study

Abstract: The awake prone position (AP) strategy for patients with acute respiratory distress syndrome (ARDS) is a safe, simple, and cost-effective technique used to improve hypoxemia. We aimed to evaluate intubation and mortality risk in patients with coronavirus disease (COVID-19) who underwent AP during hospitalisation.In this retrospective, multicentre observational study conducted between May 1 and June 12, 2020 in 27 hospitals in Mexico and Ecuador, non-intubated patients with COVID-19 managed with AP or supine po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 37 publications
4
57
1
3
Order By: Relevance
“… 6 However, early data were based on anecdotal reports and small case series. In the largest available studies of patients on a medical ward, the duration of prone positioning was often not reported, 12 and when reported it was typically less than three hours a day. 6 Most of these studies focused on oxygenation rather than clinical outcomes and identified improvements in oxygenation while the patient was prone, but improvements did not necessarily persist after prone positioning was stopped.…”
Section: Discussionmentioning
confidence: 99%
“… 6 However, early data were based on anecdotal reports and small case series. In the largest available studies of patients on a medical ward, the duration of prone positioning was often not reported, 12 and when reported it was typically less than three hours a day. 6 Most of these studies focused on oxygenation rather than clinical outcomes and identified improvements in oxygenation while the patient was prone, but improvements did not necessarily persist after prone positioning was stopped.…”
Section: Discussionmentioning
confidence: 99%
“…1 d). The largest retrospective, multicenter, observational study showed a reduction in the intubation rate in patients who received awake prone position for at least 2 consecutive hours, compared to patients who did not receive this intervention [ 124 ▪▪ ]. Three small, randomized feasibility trials available showed no benefit on endotracheal intubation rate and on mortality [ 125 , 126 , 127 ▪ ].…”
Section: New Strategies: Awake Prone Positioningmentioning
confidence: 99%
“…The APRONOX study ( 70 ), compared outcomes of patients with various sources of oxygen therapy (low-flow, high-flow, and reservoir mask) who underwent prone sessions of at least 2 h duration. The total mean duration of the prone was 12 h during the entire hospital stay and the SpO 2 /FiO 2 ratio increased significantly after the prone sessions (from 183 to 212).…”
Section: Non-invasive Support Modalities Escalating Algorithms and The Role Of Combined Therapiesmentioning
confidence: 99%